EFFECT OF PHOTON ENERGY ON THE RADIATION SENSITIVITY OF HEMA POLYMER GEL DOSIMETER BASED ON NEAR INFRARED EVALUATION - Alhassan, Muhammad; Joseph, Emmanuel; Namadi, Abdulrahman Zuru (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigates the photon energy dependence of HEMA polymer gel dosimeters (PGDs) with maltose additive, evaluated using near-infrared (IR) spectrophotometry. Two batches of PGDs with varying maltose concentrations (0–520 mM) were irradiated using 6 MV and 10 MV photon beams. Absorbance-dose response curves were plotted, and sensitivities were compared using regression analysis and ANOVA. Results indicated a significant difference in sensitivity between the two photon energies (p < 0.05), suggesting photon energy dependence in the evaluated HEMA PGDs. These findings emphasize the need for energy-specific calibration when using HEMA PGDs in clinical applications.